Academic flexibility and support for student-athletes: An Australian perspective on university teaching staff perceptions. Issue 1 (2nd January 2022) - English, Peter; Fleischman, David; Kean, Bridie; Stevenson, Tania; Broome, Kieran; Cury, Rubiana
ABSTRACT: Perspectives of teaching staff on the provision of flexibility for student-athletes are relatively unknown but are a vital element to understand when educating student-athletes. Flexibility is among the academic services often provided to athletes pursuing a dual-pathway. This study aims to investigate teaching staff perceptions on academic support services designed specifically for student-athletes. Utilizing an exploratory approach, it targets the case of one Australian university that has an agenda to support and foster student-athlete academic success. It utilizes an open-ended survey to explore teaching staff perceptions on their ability and willingness to provide learning and teaching support. Seventy-seven educators completed the survey, and the data were examined using both thematic and automated text analysis. There were varying degrees of support regarding flexibility and special considerations for student-athletes. The findings showed that developments in blended learning capability and better internal communication among university management, academics and student-athletes could facilitate improvements in student-athlete support.